Pelatihan Self-Acceptance dalam Menumbuhkan Sikap Optimisme pada Warga Binaan Lembaga Pemasyarakatan Kelas IIB Kota Probolinggo - Rasyid, Abdul (Fakultas Dakwah UIN KHAS Jember, 2023)
The objective of this study is to examine the impact of self-acceptance training on promoting optimism among inmates at Probolinggo Class IIB Correctional Facility. The sample comprised 30 inmates selected through purposive sampling, meeting the criteria of being from the Pesantren Block and having served a minimum sentence of 3 years. Utilizing a quasi-experimental approach, specifically the One-Sample Kolmogorov-Smirnov Test, the data were analyzed using paired sample t-tests. With the calculated t-test value surpassing the t-table value (7.910 > 2.042), the null hypothesis was accepted, indicating a significant influence of self-acceptance training on the optimism levels of inmates at Probolinggo Class IIB Correctional Facility. Prior to participating in self-acceptance training, the average optimism score among inmates was 94.63, which increased to 100.60 post-training. Hence, this study concludes that self-acceptance training indeed impacts the optimism levels of inmates in Probolinggo Class IIB Correctional Facility.